2013
DOI: 10.1002/term.1783
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chitosan conduit under a dynamic culture on the proliferation and neural differentiation of human exfoliated deciduous teeth stem cells

Abstract: Ex vivo engineering of artificial nerve conduit is a suitable alternative clinical treatment for nerve injuries. Stem cells from human exfoliated deciduous teeth (SHEDs) have been considered as alternative sources of adult stem cells because of their potential to differentiate into multiple cell lineages. These cells, when cultured in six-well plates, exhibited a spindle fibroblastic morphology, whereas those under a dynamic culture aggregated into neurosphere-like clusters in the chitosan conduit. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…It is shown that when chitosan is used to modify polymer scaffolds, the amount of adhesion of cells on the chitosan-modified scaffolds significantly increases. Chitosan, as a natural polymer, has suitable hydrophilicity and biocompatibility [20,31]. Structure of chitosan (because of its cationic nature and high charge density) is similar to ECM, which holds the specific interactions with macromolecules, growth factors, and receptors [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is shown that when chitosan is used to modify polymer scaffolds, the amount of adhesion of cells on the chitosan-modified scaffolds significantly increases. Chitosan, as a natural polymer, has suitable hydrophilicity and biocompatibility [20,31]. Structure of chitosan (because of its cationic nature and high charge density) is similar to ECM, which holds the specific interactions with macromolecules, growth factors, and receptors [30].…”
Section: Discussionmentioning
confidence: 99%
“…So, the blending of chitosan and synthetic polymer which has a suitable mechanical property can improve the mechanical property. PLA is a perfect synthetic polymer to prepare composite material with chitosan [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Dental pulp tissues are known to originate from migrating neural crest cells during development . Consequently, SHEDs are thought to be a key source of postnatal stem cells that can differentiate into neural cells.…”
Section: Discussionmentioning
confidence: 99%
“…Takayoshi et al have reported that SHED transplantation effectively reverses systemic lupus erythematosus‐related diseases in mouse models by increasing the number of regulatory T cells via inhibiting the proliferation of T helper 17 cells . SHEDs express a number of different neuronal and glial cell markers, such as Nestin, neuron‐specific enolase (NSE), beta III tubulin, glutamic acid decarboxylase, neuron‐specific nuclear protein, glial fibrillary acidic protein (GFAP), neurofilament medium chain, and 2′, 3′‐cyclic nucleotide‐3′‐phosphodiesterase, indicating the embryonic neural crest origin of dental pulp . SHEDs have shown great pluripotency for future tissue engineering applications such as bone regeneration .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation